Characterization of Bone-Marrow-Derived Stem Cells in Osteoporotic Models of the Rat. (9th July 2013) - Goergen, Julia; Wenisch, Sabine; Raabe, Oksana; Moritz, Andreas; Schlewitz, Gudrun; Schnettler, Reinhard; Hempel, Ute; Heiss, Christian; Arnhold, Stefan
Abstract : Osteoporotic effects observed after osteoporosis induction in the rat by combining ovariectomy (OVX) either with a defined calcium-deficient diet (OVX + Diet) or by administration of a glucocorticoid (dexamethasone) (OVX + Steroid) mimic the skeletal effects observed in humans affected by osteoporosis. In the present investigation rat MSCs have been characterized in vitro after osteoporosis has been induced for twelve weeks in rats by means of OVX + Diet (n = 5 ) and OVX + Steroid (n = 5 ). Sham-operated animals (n = 5 ) served as controls. MSCs were harvested from humerus and iliac crest and were cultured in standard medium and in osteogenic differentiation medium for studying the proliferation, migration, and differentiation capacity of the cells. Expression of CD90, CD105, runx2, osteocalcin (OC), and bone sialoprotein (BSP) was performed by using qrtPCR. Calcium deposits developed in the course of osteogenic differentiation were measured by using Pentra 400 Axon Lab. Taken together, the present results showed that osteoporosis induction leads to MSC in a state of senescence: proliferation and migration rates of the cells were diminished pointing to self-renewal deficiency and impaired motility of rat MSC in contrast to controls. However, the osteogenic differentiation capacity was increased after osteoporosis induction with OVX + Diet and OVX + Steroid.